Efficient, solvent-free method for the chemoselective synthesis of acylals from aldehydes and their deprotection catalyzed by silica sulfuric acid as a reusable solid acid catalyst - Desai, Uday V.; Thopate, T. S.; Pore, D. M.; Wadgaonkar, P. P. (Catalysis Communications, 2006)
An efficient method has been developed for the chemoselective synthesis of acylals from aldehydes and acetic anhydride in the presence of silica sulfuric acid as a reusable solid acid catalyst under solvent-free conditions. Ketones are found to remain unaffected under the reaction conditions. The deprotection of acylals has also been achieved using SSA in methanol medium. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylals; aldehydes; Chemoselective; protection and deprotection silica sulfuric acid

Efficient method for the synthesis of acylals from aldehydes under solvent-free conditions catalyzed by antimony trichloride - Bhattacharya, Asish K.; Mujahid, Mohammad; Natu, Arvind A. (Synthetic Communications, 2008)
A mild and efficient method has been developed for the preparation of acylals from aldehydes catalyzed by antimony trichloride under solvent-free conditions in very good to excellent yields. The easy availability, low cost, and ease of handling of the catalyst make this procedure especially attractive for large-scale synthesis.
Keywords: acetic anhydride; Acylals; aldehydes; antimony trichloride; solvent-free conditions

Convenient and efficient protocol for the synthesis of acylals catalyzed by bronsted acidic ionic liquids under ultrasonic irradiation - Borikar, Sanjay P.; Daniel, Thomas (Ultrasonics Sonochemistry, 2011)
The synthesis of acylals (1,1-diacetates) via the reactions of aldehydes with acetic anhydride was carried Out in 85-97% yields at room temperature under ultrasound irradiation catalyzed by the Bronsted acidic ionic liquid [bmpy]HSO(4). This method provides several advantages, such as solvent-free conditions, operational simplicity, higher yields, and reduced environmental consequences. The ionic liquid was recovered and reused. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 1-Butyl-3-methylpyridinium hydrogen sulfate; 1-Diacetates; Acylals; Ionic liquid; Solvent-free; Ultrasonic irradiation